Analisis Perbandingan Kinerja Keuangan Bank Umum Konvensional Dengan Bank Umum Syariah di Indonesia Menggunakan Metode RGEC Periode 2018-2022 - Putri Awaliana Ramdan; Lalu Hamdani Husnan; Siti Aisyah Hidayati (Postgraduate, University of Mataram, 2023)
This research aims to determine the differences in financial performance between Conventional Commercial Banks and Sharia Commercial Banks for the 2018-2022 period using the RGEC method which consists of Risk profile, Good corporate governance, Earnings and Capital. Risk Profile is proxied using the Non Performing Loans (NPL) ratio and Loan to Deposit Ratio (LDR) for BUK and Non Performing Financing (NPF) and Financial to Deposit Ratio (FDR) for BUS, GCG is proxied using the GCG self assessment composite value, Earnings are proxied using Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM) for BUK and Net Operating Margin (NOM) for BUS and BOPO, and Capital is proxied using the Capital Adequacy Ratio (CAR). The sample used in this research consisted of 10 Conventional Commercial Banks and 7 Sharia Commercial Banks. Samples were taken using a purposive sampling method based on predetermined criteria. The data analysis techniques used in this research are descriptive statistics, normality test, and Independent Sample t-Test. The results of the research show that there are significant differences between Conventional Commercial Banks and Sharia Commercial Banks in the financial performance ratios of NPL/NPF, ROA, ROE, NIM and BOPO. Meanwhile, in terms of LDR/FDR, GCG and CAR financial performance ratios, there are no significant differences between Conventional Commercial Banks and Sharia Commercial Banks.